2014
DOI: 10.3724/sp.j.1009.2013.00406
|View full text |Cite
|
Sign up to set email alerts
|

A new Amaryllidaceae alkaloid from the bulbs of Lycoris radiata

Abstract: Alkaloid 1 is a new compound, and 1-3 were major alkaloids in this plant. Alkaloids 1-3 showed weak antiviral activities against flu virus A with IC50 values of 2.06, 0.69, and 2.71 μg·mL-1 and CC50 values of 14.37, 4.79, and 80.12 μg·mL-1, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Pi et al, [60] reported that some alkaloids isolated from bulb of L. aurea showed significant cytotoxicity against all tumor cell line (seven) tested. The alkaloids 3-0-ethyltazettinol 2α-methoxy-6-O-ethyloduline have also been isolated from the bulb of L. aurea [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…Pi et al, [60] reported that some alkaloids isolated from bulb of L. aurea showed significant cytotoxicity against all tumor cell line (seven) tested. The alkaloids 3-0-ethyltazettinol 2α-methoxy-6-O-ethyloduline have also been isolated from the bulb of L. aurea [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…Professor Einstein resulted in the isolation of 23 known AA , and a new alkaloid (24). The compounds were analyzed by various spectroscopic methods (GC-MS, LC-MS, and 1D and 2D NMR spectroscopy) and identified by comparison with literature data as masonine (1) [22], homolycorine (2) [23], ismine (3) [24], caranine (4) [25], galanthamine (5) [26], narwedine (6) [27], lycoraminone (7) [28], pluviine (8) [25], incartine (9) [29], galanthine (10) [30], lycoramine (11) [26], epinorgalanthamine (12) [31], norlycoramine (13) [32], haemanthamine (14) [32], hippeastrine (15) [33], epimaritidine (16) [34], lycorine (17) [35], tazettine (18) [36], eugenine (19) [37], norpluviine (20) [38], 9-O-demethylmaritidine (21) [39], pancracine (22) [40], and 9-O-demethylhomolycorine (23) [23] (Figure 1). The alkaloids that were isolated were representatives of the homolycorine (1,2,15,19,23), galanthamine (5,6,…”
Section: Isolation and Identification Of Amaryllidaceae Alkaloids Fromentioning
confidence: 99%
“…The Lycoris genus (Amaryllidaceae) consists of more than 20 species and is mainly distributed in the temperate woodlands of eastern Asia, with 17 (including one variety) distributed in China . The bulbs have been used as herbal medicines to treat laryngeal trouble, furuncle, carbuncle, mastitis, tympanitis, ulcers, suppurative wounds and poliomyelitis in China . Lycorine, one of the most common alkaloids in Lycoris spp., and related lycorine‐type alkaloids are believed to possess antiviral, anti‐inflammatory, anticancer, antifungal and antimalarial properties.…”
Section: Introductionmentioning
confidence: 99%